Energy utilization assessment of a semi-closed greenhouse using data-driven model predictive control. (15th November 2021) - Mahmood, Farhat; Govindan, Rajesh; Bermak, Amine; Yang, David; Khadra, Carol; Al-Ansari, Tareq
Abstract: With the global increase in food demand, closed and controlled greenhouses are an essential source for year-round crop production. Maintaining the optimum conditions inside the greenhouse throughout the year is critical to improving crop quality and yield. However, greenhouses consume more resources than other commercial buildings due to their inefficient operation and structure. Therefore, a data-driven model predictive control approach for a semi-closed greenhouse is proposed for temperature control and reducing energy consumption in this study. The proposed method consists of a multilayer perceptron model representing the greenhouse system integrated with an objective function and an optimization algorithm. The multilayer perceptron model is trained using historical data from the greenhouse with solar radiation, outside temperature, humidity difference, fan speed, HVAC control as the input parameters to predict the temperature. The greenhouse model's performance is evaluated under varying scenarios, such as increasing the prediction time step and changing the number of samples in the training data set. Results illustrated that the MPC approach had a better temperature control than the greenhouse adaptive control system for winter and summer with an RMSE value of 0.33 °C and 0.36 °C, respectively. Similarly, model predictive control resulted in an energy reduction of 7.70% for winter and 16.57% for the summer season. The proposed model predictive control framework is flexible and can be applied to other greenhouse systems by tuning the model on the new data set. Highlights: A model predictive control approach is adopted for a semi-closed greenhouse. A multilayer perceptron model is used for modeling the dynamic system. Not only temperature set-point tracking but also energy consumption is considered. MPC results in superior temperature tracking and reduction in energy consumption.